Intravascular lithotripsy in calcified‐coronary lesions: A real‐world observational, European multicenter study. Issue 2 (16th September 2020) - Aziz, Amir; Bhatia, Gurbir; Pitt, Michael; Choudhury, Anirban; Hailan, Ahmed; Upadhyaya, Subramanya; Lee, Leong; Testa, Luca; Casenghi, Matteo; Ielasi, Alfonso; Cortese, Bernardo; Rides, Hannah; et al.
Abstract: Background: The recently introduced intravascular lithotripsy (IVL) appears promising and relatively safer than conventional approaches when dealing with calcified lesions. Although there are published reports on this novel technology, data from the real world are limited. In this study, we aim to report on the experience of IVL from a real‐world population derived from six European centers that undertake high‐volume complex coronary interventions. Methods and results: We enrolled all patients treated with IVL between November 2018 and February 2020 at six centers. Procedural success and complications were assessed along with clinical outcomes, which included: cardiac death, target vessel myocardial infarction (TVMI), target lesion revascularisation (TLR), and major adverse cardiac event (MACE) (composite of cardiac death, TVMI, and TLR). Hundred and ninety patients (200 lesions) with a mean age of 72 years were treated using IVL. Diabetes and chronic kidney disease were present in 50% ( n = 95) and 16% ( n = 30) of cases, respectively. Acute‐coronary syndromes accounted for 91 (48%) of the cases. Most were de‐novo lesions (77%; n = 154). Upfront use of IVL occurred in 26% of cases, while the rest were bail‐out procedures due to inadequate predilatation with conventional balloons. Adjuvant rotational atherectomy was needed in 17% of cases. Procedural success was achieved in 99% of cases with a complication rate of 3%. During the median follow‐up of 222 days, there was two cardiac deaths (1%), one case of TVMI (0.5%), 3 TLR (1.5%) taking the MACE rate to 2.6%. Conclusion: Use of IVL appears to be safe and effective in dealing with calcified‐coronary lesions. A high success rate was observed with low procedural complications and event rates.